The Role of Sustainable Practices in Enhancing Customer Loyalty: The Case of a Finnish travel company - Munir, Ramsha (My University, 2026)
Within the tourism industry, particularly in places that are highly environment conscious and well regulated, the issue of sustainability has assumed the frontline position in the strategic concerns of the tourism industry. The thesis will analyze the role of sustainable practices principle in customer loyalty in the Finnish tourism context through the Haltia Lake Lodge as a qualitative case study. The study is based on an interpretivist-constructivist paradigm. It is based on the Theory of Planned Behavior and the Theory of Stakeholder to study the perception, experiences and evaluation of sustainability by the key stakeholders of the company. Semi-structured interviews with customers, employees, and the top management were used to acquire the data. The thematic analysis was conducted to find common patterns and meanings in the sources of data. The evidence demonstrates that sustainability is more of a set of practicality, observable and institutionalized practices, as opposed to a strategic formalism. Sustainable practices seem to increase customer satisfaction and trust, but they are more of a complementary than a driving force behind loyalty. The combination of the factors of experience, including place, atmosphere, quality of service and value fit, results in customer loyalty, and the factor of sustainability contributes to the other factors indirectly. The research contributes to the body of knowledge on sustainable tourism, with a context-specific result in Finland. It underlines the importance of genuineness, sensitive communication, and involvement of employees in the process of converting sustainability into substantial experiences by customers. The implication on real practice, such as how the concept of sustainability can be integrated by tourism managers in the long-term relationship building strategies is discussed.
Keywords: sustainable development; case study; green economy; Finland; customer loyalty; customer satisfaction; sustainable tourism; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business